Impact of Conyza bonariensis density and establishment period on soyabean grain yield, yield components and economic threshold. (12th November 2014) - Trezzi, M M; Vidal, R A; Patel, F; Miotto, E; Debastiani, F; Balbinot, A A; Mosquen, R; Ghersa, Claudio
Summary Conyza spp. have become a major weed around the world, mainly because of weed resistance issues. The objective of this work was to test the hypothesis that the soyabean crop yield is dependent on the density of Conyza bonariensis and on the timing of weed establishment in relation to the crop sowing date. It was also theorised that these variables affect soyabean crop yield components and the economic threshold of C. bonariensis on soyabean. Field experiments were conducted during 2010 and 2011 using a randomised complete block design. In each experiment, several densities (0, 3, 6, 12, 24, 48, 96 and 192 plants m−2) of C. bonariensis were established in soyabean fields. Conyza bonariensis establishment dates varied considerably between the experiments [81, 38 and 0 days before soyabean sowing (DBSS)]. Conyza bonariensis plants were first cultivated in a glasshouse and then transplanted to the field at the three‐leaf growth stage. At the lower densities, each C. bonariensis plant decreased soyabean yield by 36%, 12% and 1.0%, when established at 81, 38 and 0 DBSS respectively. The economic thresholds based on sensitivity analysis were below 0.5 plant m−2 when C. bonariensis was introduced at 81 and 38 DBSS; in contrast, they were between 2 and 4 plants m−2 when the weed was established at the crop sowing time. The results emphasise the importance of proper C. bonariensis management prior to soyabean sowing and highlight the need for residual herbicides to avoid grain yield losses.